Strategies to Promote Entrepreneurship: A comparative overview of strategies implemented in South Africa, India and Brazil. - Wilkinson, Andrew (The IIE, 2017)
Entrepreneurial promotion is essential for a country’s ability to develop their entrepreneurial rate using various strategies. South Africa, India and Brazil are all members of the BRICS association with similarities in; economies, political situations, larger populations and vast amounts of lands. However, they all have different entrepreneurial rates due to their individual strategies for entrepreneurship promotion, of which South Africa’s is significantly lower. Information on each of these countries was gathered using secondary data from credible sources in a cyclical manner, ensuring trustworthy results. The four general strategies that emerged from previous data were; literacy rates and human capital, education and training of entrepreneurs, access to capital and raw materials, and institutional support. Individual and unique strategies that fell under these categories were found in the above-mentioned BRICS partners and were explored in detail in the form of a comparative case study approach. Therefore, this interpretivist study utilises qualitative techniques in a cross-sectional manner. South Africa’s entrepreneurial rate is significantly lower than their partner BRICS countries enabling the country to learn from the successes and failures of India and Brazil through the utilisation of the knowledge available, to better their own entrepreneurial rate.
Keywords: BRICS; Entrepreneurship; Entrepreneurial promotion; Institutional support